Mechanical mapping and morphology across the length scales unveil structure–property relationships in polycaprolactone based polyurethanes. Issue 22 (10th August 2016) - Gojzewski, Hubert; Imre, Balazs; Check, Casey; Chartoff, Richard; Vancso, Julius
ABSTRACT: Segmented polyurethane elastomers for biomedical applications were synthesized and studied at macroscopic (by mechanical testing) and meso/nanoscopic length scales (by atomic force microscopy, AFM). The polyurethanes are composed of 4, 4'‐methylenebis(phenyl isocyanate), 1, 4‐butanediol and an ε‐polycaprolactone diol. The stoichiometric ratio of the isocyanate and hydroxyl groups is constant, but the polymer diol to total diol—varies from 0 to 100 %. We show the representative features of the morphology from phase separation to mixed phases, how this is related to the mechanical properties in the bulk and locally, at exposed free surfaces and at the nanoscale. We propose a morphological model considering the molecular structure, the length of hard segments, and the dimensions of both the soft and the hard phases, respectively. Understanding such structure–property relations is pivotal to establishing designer materials and controlling the performance of the final product to achieve optimal properties in polyurethane based medical devices. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 2298–2310. Abstract : The structure–property relationships of ε‐polycaprolactone‐based elastomer polyurethanes have been investigated at macroscopic (standard mechanical testing) and meso/nanoscopic length scales (elastic modulus and adhesion force quantitative AFM maps). A morphological model is proposed considering the molecular structure, the length of hard segments, and the dimensions of both the soft and the hard phases, respectively.